A comparative study between treadmill running and water running in two different depths - Silva Filho, Jaime Rodrigues da; Fernandes, Josiane Regina Pejon; Costa, Paula Hentschel Lobo da (Brazilian journal of physical education and sport, 2005)
Deep water running has increased in popularity as a mode of exercise. Biomechanical studies on deep water running are important because they would explain whether the techniques used during deep and shallow water running can really be considered mechanically similar to that of running on land. Thus, the purpose of this study was to compare the spatio-temporal variables and body positions of deep water, shallow water and treadmill running techniques. Three males and three females experienced in deep water running volunteered to this study. A bidimensional approach was performed using video analysis. Sagital plane images were recorded with an underwater view of the water running techniques. Two velocities were tested: self-selected and maximal. The discussion made concerns the changes in the running pattern that were considered as effects of the mechanical characteristics of the water environment and of the absent of ground contact during deep water running